Internal Proportions of The Body Composition in Members of the Female National Tennis Team of Poland (Baltic Journal of Sport and Health Sciences, 2018)
Contemporary anthropological research confirms the fact that body composition is one of the basic elements differentiating athletes from persons not practising sport. Among athletes representing various branches of sport there are also significant differences in their body composition. Internal proportions of the body composition of an athlete, or a selected group of athletes, is an especially important yet little researched issue of sports anthropology. This problem is still topical in sports games, especially in tennis. Therefore, the aim of the study was to determine internal proportions of the body composition of female tennis players from the Polish national team in comparison to persons who do not practice sport professionally. The study involved female athletes of the Polish national tennis team (n = 10). The study was carried out in a training camp from 28 September to 9 October 2002 in Zakopane — Centre of Sports Preparation. Athletes’ age was 16—20 (18.1 ± 1.4) years, and the training experience 8—12 years (10.5 ± 1.8). The mean body height for the group members was 171.9 ± 6.7 cm and the mean body mass 59.7 ± 6.3 kg. The results of research by Piechaczek et al. (1996) constituted the reference point for the results of measurements of Polish tennis representatives. The authors studied 153 female students of Warsaw Technical University aged 20.2 ± 1.09 years. They were randomly chosen students of the first and the second year of various departments at this university. The mean body height of the students was 166.2 ± 6.2 cm and the mean body mass 57.4 ± 7.72 kg. Anthropometric measurements were taken using standard instruments (Drozdowski, 1998). The analysis involved 11 somatic features which determined three so-called factors of body composition: length (m1), stoutness (m2) and obesity (m3). The assessment of proportions of the body composition was made by means of Perkal’s natural indices (1953) with Milicerowa’s modifications (1956). We determined the following: composition factors (m), index of total body size (M), internal proportions of the body composition, evenness of composition, the code of internal proportions; also the assessment of internal proportions of the body composition within each of the factors.Taking into consideration the mean values of the studied somatic features in the control group and the comparative group we found differences in their body composition. The representatives of the Polish national tennis team showed substantially longer upper and lower limbs, and the body height was greater. They also had much greater forearm perimeter and shorter pelvic width. As to the total body size, the tennis players slightly exceeded the students (M = 0.24). The total body size (M) resulted from high values of length features (m1 = 1.01), low ones of stoutness (m2 = –0.39) and medium ones of obesity (m3 = 0.1). The value of the intragroup variability index (harmony of composition) amounted to 1.4 and the code of internal proportions of tennis players’ body composition — to 6—2—4. The proportions of internal features of the stoutness index (natural indices of features within a factor) showed the advantage of the forearm perimeter (1.62) and elbow width (0.36). The knee width (–1.30) and pelvic width (–0.60) were disproportionate to the total value of this factor. The input of features characterizing the length factor was relatively proportional.Keywords: tennis, training, body composition, internal proportions.